(untitled) (Konferensiyalar | Conferences, 2024)
This thesis analyzes the greeting and farewell phrases in both Uzbek and English languages to explore the cultural intricacies and social conventions inherent in these expressions. By delving into the traditional customs and linguistic patterns of these languages, this research illustrates the cultural diversity and richness of human communication practices.